“Sorry, Too Much Information”. Designing Online Review Systems that Support Information Search and Processing - Seutter, Janina; Kutzner, K.; Stadtländer, M.; Kundisch, Dennis; Knackstedt, R. (Electronic Markets)

Verdrängen Smart-Product-Service-Systeme die Interaktion in Online-Communities? – Empirische Evidenz aus einer Rezept-Community - Seutter, Janina; Müller, Michelle; Kundisch, Dennis (Wirtschaftsinformatik & Management)

Business Models for Cultural Event Platforms - A Taxonomy Approach - Althaus, Maike; Grieger, Nicole; Vorbohle, Christian; Müller, Michelle; Kundisch, Dennis (Proceedings of the 15th Mediterranean Conference on Information Systems (MCIS))

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A general Best-Worst method considering interdependency with application to innovation and technology assessment at NASA - Tavana, Madjid; Mina, Hassan; Santos-Arteaga, Francisco J. (Journal of Business Research)
Keywords: Marketing

Analytical hierarchy process: revolution and evolution - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J. (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A fuzzy preference programming and weighted influence non-linear gauge system for mission architecture assessment at NASA - Tavana, Madjid; Heidary, Mohammad Saeed; Mina, Hassan (Applied Soft Computing)
Keywords: Software

A Credibility and Strategic Behavior Approach in Hesitant Multiple Criteria Decision-Making With Application to Sustainable Transportation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; Tena, Emilio Cerda (IEEE Transactions on Fuzzy Systems)
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Control and Systems Engineering

Value Chain digitalization and technological development as innovation catalysts in small and medium-sized enterprises - Marín, Raquel; Santos-Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora (Journal of Innovation & Knowledge)
Keywords: Management of Technology and Innovation; Marketing; Economics and Econometrics; Business and International Management

An integrated decision support framework for resilient vaccine supply chain network design - Tirkolaee, Erfan Babaee; Torkayesh, Ali Ebadi; Tavana, Madjid; Goli, Alireza; Simic, Vladimir; Ding, Weiping (Engineering Applications of Artificial Intelligence)
Keywords: Electrical and Electronic Engineering; Artificial Intelligence; Control and Systems Engineering

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Spacecraft tracking control and synchronization: An assessment of conventional, unconventional, and combined methods - Deveci, Muhammet; Pamucar, Dragan; Gokasar, Ilgin; Tavana, Madjid (Advances in Space Research)
Keywords: Space and Planetary Science; Aerospace Engineering; General Earth and Planetary Sciences; Atmospheric Science; Geophysics; Astronomy and Astrophysics

A novel median-based optimization model for eco-efficiency assessment in data envelopment analysis - Dellnitz, Andreas; Tavana, Madjid; Banker, Rajiv (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A combinatorial data envelopment analysis with uncertain interval data with application to ICT evaluation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid (Technological Forecasting and Social Change)
Keywords: Management of Technology and Innovation; Applied Psychology; Business and International Management

A novel indicator for sustainability in production planning using Center of Gravity-based assessment of Pareto fronts - Hilbert, Markus; Dellnitz, Andreas; Kleine, Andreas; Tavana, Madjid (Computers & Industrial Engineering)
Keywords: General Engineering; General Computer Science

From classical interpretive structural modeling to total interpretive structural modeling and beyond: A half-century of business research - Sorooshian, Shahryar; Tavana, Madjid; Ribeiro-Navarrete, Samuel (Journal of Business Research)
Keywords: Marketing

A new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps - Namazi, Mehdi; Tavana, Madjid; Mohammadi, Emran; Bonyadi Naeini, Ali (Benchmarking: An International Journal)
Purpose New business practices and the globalization of markets force firms to take innovation as the fundamental pillar of their competitive strategy. Research and Development (R&D) plays a vital role in innovation. As technology advances and product life cycles become shorter, firms rely on R&D as a strategy to invigorate innovation. R&D project portfolio selection is a complex and challenging task. Despite the management's efforts to implement the best project portfolio selection practices, many projects continue to fail or miss their target. The problem is that selecting R&D projects requires a deep understanding of strategic vision and technical capabilities. However, many decision-makers lack technological insight or strategic vision. This article aims to provide a method to capitalize on the expertise of R&D professionals to assist managers in making informed and effective decisions. It also provides a framework for aligning the portfolio of R&D projects with the organizational vision and mission. Design/methodology/approach This article proposes a new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps. Findings The proposed strategy plane helps decision-makers align R&D project portfolios with their strategies to combine a strategic view and numerical analysis in this research. The proposed strategy plane consists of four areas: Exploitation Zone, Challenge Zone, Desperation Zone and Discretion Zone. Mapping the project into this strategic plane would help decision-makers align their project portfolio according to the corporate perspectives. Originality/value The new approach combines the efficiency and uncertainty dimensions in portfolio selection into an integrated framework that: (i) provides a complete representation of the stochastic decision-making processes, (ii) models the endogenous uncertainty inherent in the project selection process and (iii) proposes a computationally practical and visually unique solution procedure for classifying desirable and undesirable R&D projects.
Keywords: Business and International Management; Strategy and Management

A comparative performance analysis of intelligence-based algorithms for optimizing competitive facility location problems - Hajipour, Vahid; Niaki, Seyed Taghi Akhavan; Tavana, Madjid; Santos-Arteaga, Francisco J.; Hosseinzadeh, Sanaz (Machine Learning with Applications)
Keywords: General Medicine

A Game-Theoretic Framework for Analyzing the Impact of Social Responsibility and Supply Chain Profitability - Mahdiraji, Hannan Amoozad; Tavana, Madjid; Rezayar, Ali (Cybernetics and Systems)
Keywords: Artificial Intelligence; Information Systems; Software

Designing digital actor engagement platforms for local high streets: an action design research study - Bartelheimer, Christian; zur Heiden, Philipp; Berendes, Carsten Ingo; Beverungen, Daniel (European Journal of Information Systems)
High streets across Europe continue to lose consumers to online retail, leading to business closures and the decline of city centres, impairing cities’ overall liveability. To counter this vicious cycle, our study presents smartmarket2, the first instantiation of a digital actor engagement platform designed specifically for high streets. smartmarket2 enables hybrid online-offline customer journeys by connecting consumers to stores and other high street service providers. In an action design research (ADR) project, we design, implement and evaluate smartmarket2, involving 150 high street operators and 2,300 citizens in three cycles of building, intervention and evaluation. We derive four design principles that contribute prescriptive knowledge on the design of digital actor engagement platforms. Our results reveal that such a platform is able to increase engagement, but that it is subject to actors’ engagement dispositions.
Keywords: Digital platform; action design research; design principles; actor engagement; engagement platform; location-based advertising

An integrated group fuzzy inference and best–worst method for supplier selection in intelligent circular supply chains - Tavana, Madjid; Sorooshian, Shahryar; Mina, Hassan (Annals of Operations Research)

A fuzzy multi-objective optimization model for sustainable location planning using volumetric fuzzy sets - Tavana, Madjid; Arman, Hosein; Hadi-Vencheh, Abdollah; Mansoori, Sadegh (Annals of Operations Research)

Information and Communication Technologies and Labor Productivity: A Dynamic Slacks-Based Data Envelopment Analysis - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid (Journal of the Knowledge Economy)

A sustainable circular supply chain network design model for electric vehicle battery production using internet of things and big data - Tavana, Madjid; Sohrabi, Mahsa; Rezaei, Homa; Sorooshian, Shahryar; Mina, Hassan (Expert Systems)

A hesitant fuzzy group decision-making framework with data credibility and strategic evaluations - Tavana, Madjid; Keikha, Abazar; Santos-Arteaga, Francisco J. (Soft Computing)

An optimization model with a lagrangian relaxation algorithm for artificial internet of things-enabled sustainable circular supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Santos-Arteaga, Francisco J.; Saberi, Esmaeel; Mina, Hassan (Annals of Operations Research)

Dear Guests, please pay for my license – Analyzing the heterogenous cost-pass-through of commercial and non-commercial rental suppliers in response to regulatory policies - Müller, Michelle; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Moment or Movement – An Empirical Analysis of the Heterogeneous Impact of Media Attention on Charitable Crowdfunding Campaigns - Seutter, Janina; Müller, Michelle; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Utilizing Geographic Information Systems for Condition-Based Maintenance on the Energy Distribution Grid - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

Context in Design Science Research: Taxonomy and Framework - Herwix, Alexander; zur Heiden, Philipp (Proceedings of the 55th Hawaii International Conference on System Sciences)

A Renaissance of Context in Design Science Research - zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

Exploring purposes of using taxonomies - Schoormann, T.; Möller, F.; Szopinski, Daniel (Tagungsband der 17. Internationalen Tagung Wirtschaftsinformatik 2022)

Visual Interpretability of Image-based Real Estate Appraisal - Kucklick, Jan-Peter (55th Annual Hawaii International Conference on System Sciences (HICSS-55))
Explainability for machine learning gets more and more important in high-stakes decisions like real estate appraisal. While traditional hedonic house pricing models are fed with hard information based on housing attributes, recently also soft information has been incorporated to increase the predictive performance. This soft information can be extracted from image data by complex models like Convolutional Neural Networks (CNNs). However, these are intransparent which excludes their use for high-stakes financial decisions. To overcome this limitation, we examine if a two-stage modeling approach can provide explainability. We combine visual interpretability by Regression Activation Maps (RAM) for the CNN and a linear regression for the overall prediction. Our experiments are based on 62.000 family homes in Philadelphia and the results indicate that the CNN learns aspects related to vegetation and quality aspects of the house from exterior images, improving the predictive accuracy of real estate appraisal by up to 5.4%.
Keywords: Explainable Artificial Intelligence (XAI); Regression Activation Maps; Real Estate Appraisal; Convolutional Block Attention Module; Computer Vision

Using Geolocated Text to Quantify Location in Real Estate Appraisal - Heuwinkel, Tim; Kucklick, Jan-Peter; Müller, Oliver (55th Annual Hawaii International Conference on System Sciences (HICSS-55))
Accurate real estate appraisal is essential in decision making processes of financial institutions, governments, and trending real estate platforms like Zillow. One of the most important factors of a property’s value is its location. However, creating accurate quantifications of location remains a challenge. While traditional approaches rely on Geographical Information Systems (GIS), recently unstructured data in form of images was incorporated in the appraisal process, but text data remains an untapped reservoir. Our study shows that using text data in form of geolocated Wikipedia articles can increase predictive performance over traditional GIS-based methods by 8.2% in spatial out-of-sample validation. A framework to automatically extract geographically weighted vector representations for text is established and used alongside traditional structural housing features to make predictions and to uncover local patterns on sale price for real estate transactions between 2015 and 2020 in Allegheny County, Pennsylvania.
Keywords: Real Estate Appraisal; Text Regression; Natural Language Processing (NLP); Location Intelligence; Wikipedia

DASC-PM v1.1 - Ein Vorgehensmodell für Data-Science-Projekte - Schulz, Michael; Neuhaus, Uwe; Kaufmann, Jens; Kühnel, Stephan; Alekozai, Emal M.; Rohde, Heiko; Hoseini, Sayed; Theuerkauf, René; Badura, Daniel; Kerzel, Ulrich; Lanquillon, Carsten; Daurer, Stephan; et al.

Three Layers of Abstraction—A Conceptual Framework for Theorizing digital Multi-Sided Platforms - Poniatowski, Martin; Lüttenberg, Hedda; Beverungen, Daniel; Kundisch, Dennis (Information Systems and e-Business Management, Special Issue on Platform Business Models and Platform Strategies)

Smart Service für die prädiktive Instandhaltung zentraler Komponenten des Mittelspannungs-Netzes - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Forum Dienstleistungsmanagement)

Methoden zum Design digitaler Plattformen, Geschäftsmodelle und Service-Ökosysteme - Robra-Bissantz, Susanne; Lattemann, Christoph; Laue, Ralf; Leonhard-Pfleger, Raphaela; Wagner, Luisa; Gerundt, Oliver; Schlimbach, Ricarda; Baumann, Sabine; Vorbohle, Christian; Gottschalk, Sebastian; Kundisch, Dennis; Engels, Gregor; et al. (HMD Praxis der Wirtschaftsinformatik)

Tackling Crises Together? – An Econometric Analysis of Charitable Crowdfunding During the COVID-19 Pandemic - Althaus, Maike; Poniatowski, Martin; Kundisch, Dennis (Proceedings of the 43rd International Conference on Information Systems (ICIS))

May I have your attention, please? Analyzing the effects of attention screening mechanisms on crowdworking platforms - Laux, Florian; Poniatowski, Martin; Kundisch, Dennis

Online Reviews in B2B Markets: A Qualitative Study on the Underlying Motives - Seutter, Janina

Online Reviews in B2B Markets: A Qualitative Study of Underlying Motivations - Seutter, Janina (Proceedings of the 30th European Conference on Information Systems (ECIS))

How the Display of the Transaction Count Affects the Purchase Intention - Poniatowski, Martin (Proceedings of the 28th Americas Conference on Information Systems (AMCIS))

Overcoming Silos: A Review of Business Model Modeling Languages for Business Ecosystems - Vorbohle, Christian; Kundisch, Dennis (Proceedings of the 30th European Conference on Information Systems (ECIS))

Tackling Crises Together? - An Econometric Analysis of Charitable Crowdfunding During the COVID-19 Pandemic - Althaus, Maike; Poniatowski, Martin; Kundisch, Dennis

Key Properties of Sustainable Business Ecosystem Relationships - Vorbohle, Christian; Kundisch, Dennis

Rollercoaster of Emotions – A Semantic Analysis of Fundraising Campaigns over the Course of the Covid-19 Pandemic - Grieger, Nicole; Seutter, Janina; Kundisch, Dennis (Tagungsband der 17. Internationalen Tagung Wirtschaftsinformatik 2022)

Modeling Business Models: A cross-disciplinary Analysis of Business Model Modeling Languages and Directions for Future Research - Szopinski, Daniel; Massa, Lorenzo; John, Thomas; Kundisch, Dennis; Tucci, Christopher (Communications of the Association for Information Systems)